Plastic collapse load analysis for circumferential cracked cylinder under pure torsion - Sutham Arun (2018)
© The Authors. This paper aims to analyze the plastic collapse moment of circumferential cracked cylinder under pure torsion using the NSC approach and 3D FE model. The material considered in this work is assumed to be elastic-perfectly plastic. The influences of geometric parameters of crack and cylinder, such as Rm/t,a/t and θ /π on solution of plastic collapse load are also investigated. The analysis shows that for the case of a/t < 0.75, the values of limit torsion moment can be estimated by NSC analysis which provides conservative results. However, for the case of deeper crack, a/t ≥ 0.75, the limit load solution predicted by NSC approach may not be safe, because the distribution of stress at yielding state does not correspond to the NSC assumption. Therefore, the approximated solution of collapse torsion moment for the case of deeper crack with a/t ≥ 0.75 is proposed based on FE analysis.